PENGABDIAN PARTISIPATIF MELALUI KEGIATAN POSYANDU YANG EFEKTIF DAN EFISIEN DI BANJAR PEKANDELAN SANUR KAUH DESA ADAT INTARAN DENPASAR SELATAN - A.A. Kade Sri Yudari; I Wayan Aribawa Wiguna; I Made Pasek Kartana; Ni Kadek Widiantari; I Putu Widiartha; Ketut Intan Tirtawati (Universitas Hindu Indonesia, 2023)
With the limited integrated healthcare center in Banjar Pekandelan in Intaran Traditional Village, Sanur Kauh Village, South Denpasar District, Denpasar City, it is the cause of inefficient services, in serving the surrounding community. So that the participatory service program as an option to contribute to the success of posyandu service activities. The method of implementation in this Integrated Healthcare Center social service activity is by requesting permission from the head or chairman of the Posyandu, then after obtaining permission, discussions and concrete actions are carried out in the activity. 100% of the activities are to directly follow the integrated Healthca re Center social service carried out by the KKN 5 UNHI 2023 group, with the results of the activity program being that the integrated healthcare center activity service can run well and all the people who follow get good and satisfying integrated healthcare Center health treatment. Keyword: Integrated Healthcare Center, Participatory service,Banjar Pekandelan, Intaran Traditional Village